Colour and water content detection of sweet cherry by portable spectrometer - Nagy, A.; Tamás, J.; Soltész, M.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2011)
Based on the most recent data, the average amount of sweet cherry produced in Hungary is around 10-12 thousand tons. Therefore fast and effective method is important for sweet cherry fruit quality analyses. The aim of the study was to examine the applicability of reflectance measurements for sweet cherry fruit quality analyses. In our experiment five cherry species (Vera, Cristalina, Germersdorfi, Noir de Mechet, Canada Giant) were examined in order to measure the spectral differences between species. Further more, spectral alteration was examined between different health and maturity status of the fruits in the case of a specified, the Germesdorfi species. The four new indices are appropriate tools for cherry quality analysis. Thus reflectance measurements can also support more precise and automated fruit selections. The methods for the differentiation of species could also be viable at a concerned habitat; however, the climate, habitat and soil conditions strongly affect the yield quality. Concerning the fast determination of water content, WBI could be a reliable method for the assessment